Improvement of protection for WEB resources from attacks based on combined heuristic and statistical approach - Prysiazhnyi, D. P. (Інститут проблем реєстрації інформації НАН України, 2016)
It is demonstrated the description of an improvement of protection for WEB resources from attacks. The improvement is based on the combined using of both heuristic and statistical approaches. The protection utilizes a classification of the most common attacks, the probability of an attack and heuristic methods for selecting countermeasures. Tabl.: 1. Fig.: 1. Refs: 14 titles.